Symptomatic Isolated Pleural Effusion as an Atypical Presentation of Ovarian Hyperstimulation Syndrome - Christine M. Mullin; M. Elizabeth Fino; Andrea Reh; Jamie A. Grifo; Frederick Licciardi (Case Reports in Obstetrics and Gynecology)
Ovarian hyperstimulation syndrome (OHSS) presents in ~33% of ovarian stimulation cycles with clinical manifestations varying from mild to severe. Its pathogenesis is unknown. Pleural effusion is reported in ~10% of severe OHSS cases and is usually associated with marked ascites. The isolated finding of pleural effusions without ascites, as the main presenting symptom of OHSS is not frequently reported and its pathogenesis is also unknown. We describe two unusual cases of OHSS where dyspnea secondary to unilateral pleural effusion was the only presenting symptom. By reporting our experience, we would like to heighten physicians' awareness in detecting these cases early, as it is our belief that the incidence of pleural effusion in the absence of most commonly recognized risk factors for OHSS may be underestimated and may significantly compromise the health of the patient if treatment is not initiated in a reasonable amount of time.